Effect of robust torus on the dynamical transport - Martins, Caroline G. L. [UNESP]; de Carvalho, R. Egydio [UNESP]; Caldas, I. L.; Roberto, M. (Iop Publishing Ltd, 2010)
In the present work, we quantify the fraction of trajectories that reach a specific region of the phase space when we vary a control parameter using two symplectic maps: one non-twist and another one twist. The two maps were studied with and without a robust torus. We compare the obtained patterns and we identify the effect of the robust torus on the dynamical transport. We show that the effect of meandering-like barriers loses importance in blocking the radial transport when the robust torus is present.